Evaluation of fundamental frequency in individuals with normal voice and those with vocal nodules - Mahshid Aghajanzade; Maryam Nikravesh (Vesnu Publications, 2011)
Introduction: Vocal nodules are non-malignant lesions of vocal cords caused by vocal misuse and abuse. Nodules can be viewed as the reaction of vocal tissue to a constant stress induced by frequent and severe movements. Acoustic signs of people with vocal fold nodules somehow differ from those with normal voice. However, there is no universal agreement on the exact amount difference between acoustics of normal voice and pathologic voice heard at the presence of vocal nodule and this, in turn, has resulted in different reported acoustic measurements. In this study, we used the standardized Rangin Kaman passage for vocal assessment of normal people and patients with voice nodule. Materials and Methods: In a cross-sectional descriptive- analytical study, 20 people with normal voice (10 males and 10 females) and 20 patients with vocal nodules (10 males and 10 females) with an age range of 40 to 59 years were randomly assigned into two age groups of 40 to 59 and 50 to 59 years. Each of these age groups included 10 subjects with normal voice (5 males and 5 females) and 10 ones with bilateral vocal nodules (5 males and 5 females). Thus, 20 voice samples were obtained from each age group. These voice samples were acoustically compared to each other on the basis of fundamental frequency and fundamental frequency variation range. Results: Results showed that the differences in fundamental frequencies was significant when all samples were considered (P = 0.043). For detecting local differences, repeated analysis of variance was performed for men and women separately. In men, significant differences of fundamental frequency were neither observed between normal and pathological samples nor between two age groups as a whole (P = 0.59). In women, differences of mean in fundamental frequency between two age groups were significant (P = 0.007). Conclusion: Mean fundamental frequency analysis can discriminates between normal voice and voice with nodules only in 50 to 59-year age group. Although nodules were recognizable through stroboscope, acoustic signs varied depending on the amount of influence exerted by the nodule on the voice. Keywords: Speech fundamental frequency, Fundamental frequency variation range, Voice, Nodules